2008
DOI: 10.1126/science.1149860
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Energy Harvesting: Generating Electricity During Walking with Minimal User Effort

Abstract: We have developed a biomechanical energy harvester that generates electricity during human walking with little extra effort. Unlike conventional human-powered generators that use positive muscle work, our technology assists muscles in performing negative work, analogous to regenerative braking in hybrid cars, where energy normally dissipated during braking drives a generator instead. The energy harvester mounts at the knee and selectively engages power generation at the end of the swing phase, thus assisting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
454
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 657 publications
(463 citation statements)
references
References 14 publications
5
454
2
2
Order By: Relevance
“…Although electricitygenerating technologies have been developed for two hundred years, people have never ceased to explore new methods through different mechanisms including photoelectric effect [1][2][3] , piezoelectric effect [4][5][6] , thermoelectric effect [7][8][9] , electrochemical reaction [10][11][12] and electrostatic induction [13][14][15] , among others, in order to address the rapidly rising demand on electric power. Among them, harvesting mechanical energy is attracting increasing attentions due to the extensive availability of the target resource [16][17][18][19][20][21][22][23][24][25] . Recently we have introduced a new concept on the basis of triboelectrification for harvesting energy from various ambient mechanical motions [26][27][28] .…”
mentioning
confidence: 99%
“…Although electricitygenerating technologies have been developed for two hundred years, people have never ceased to explore new methods through different mechanisms including photoelectric effect [1][2][3] , piezoelectric effect [4][5][6] , thermoelectric effect [7][8][9] , electrochemical reaction [10][11][12] and electrostatic induction [13][14][15] , among others, in order to address the rapidly rising demand on electric power. Among them, harvesting mechanical energy is attracting increasing attentions due to the extensive availability of the target resource [16][17][18][19][20][21][22][23][24][25] . Recently we have introduced a new concept on the basis of triboelectrification for harvesting energy from various ambient mechanical motions [26][27][28] .…”
mentioning
confidence: 99%
“…However, Mooney et al (2014) showed that it is possible to make a fully autonomous exoskeleton that assists plantarflexion and that can reduce the metabolic power of loaded walking with 8% versus normal walking if the design of the device is altered in order to reduce distal mass. Furthermore, there is increasing progress in energy recycling approaches (Collins and Kuo 2010;Donelan et al 2008;Li et al 2009;Malcolm et al 2013, Unal et al 2012) and soft exosuits (Wehner 2013), which makes it likely that autonomous ankle-foot exoskeletons can become a permanent fixture in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these values will vary between participants; for example an individual who has more pronounced movements would expect to have comparatively larger acceleration magnitudes. In order to permit effective comparison of orientation between participants, a concept of normalized power is introduced (8).…”
Section: A Analyzing the Effect Of Orientationmentioning
confidence: 99%
“…These energy sources are power constrained, that is they can theoretically provide unlimited energy over an infinite period of time, yet only very limited power can be obtained at any particular time. Such human-powered energy harvesters (referred to as microgenerators) can extract energy from a range of sources [5], including body-heat [6], forces directly applied by the body (for example footfall [7], or joint movements [8] [9]), or the inertia of the human body [10]. It is the latter of these that we focus on in this paper.…”
mentioning
confidence: 99%